2017
DOI: 10.1111/cjag.12138
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Consumer Preferences for Pig Production Attributes in Canada

Abstract: 477 478 CANADIAN JOURNAL OF AGRICULTURAL ECONOMICS de porc de production traditionnelle est importante,à la fois pour les consommateursà grande et faible confiance. La plus importante proportion de répondantsà confianceélevée se disant en faveur de cette caractéristique de confiance suggère que sa disponibilité au sein du marché pourrait nécessiter de considérables efforts pour convaincre les répondants démontrant une plus faible confiance de sa valeur ajoutée.1 http://www.schneiders.ca/products/by-brand/count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Muringai, Goddard, Bruce, Plastow, and Ma () included a Canadian Pork label and a Certified Quality Assurance label in their analysis and found that those labels generated positive and statistically significant coefficients (and willingness to pay [WTP]) in most of the models estimated, suggesting that the Verified Canadian Pork label in this study might have similar effects.…”
Section: Consumer Preferences For Functional Foodmentioning
confidence: 75%
“…Muringai, Goddard, Bruce, Plastow, and Ma () included a Canadian Pork label and a Certified Quality Assurance label in their analysis and found that those labels generated positive and statistically significant coefficients (and willingness to pay [WTP]) in most of the models estimated, suggesting that the Verified Canadian Pork label in this study might have similar effects.…”
Section: Consumer Preferences For Functional Foodmentioning
confidence: 75%
“…A set of well-established measures for generalized trust exists (e.g., measuring the extent of agreement/disagreement with statements such as "People can be trusted," "You can't be too careful in dealing with people"). While Muringai et al (2017) find that generalized trust (trust in people) influences willingness to pay for traditionally raised pork in Canada, in contrast Grebitus et al (2015) find that generalized trust does not have a strong influence on preferences for carbon footprint labels in Germany (instead finding human values offer more explanatory power). This suggests that we have more to learn about the effect of trust on consumer responses to credence attributes and the way in which those quality attributes are verified and communicated.…”
Section: Trustmentioning
confidence: 81%
“…While there are numerous approaches to defining and measuring trust, two prominent categories are institutional trust (trust in regulatory systems, food industry players) and generalized trust (trust in others or personalized trust) (Hobbs & Goddard, 2015). Variations on these measures of institutional trust have been used extensively in the context of food safety (Muringai, Goddard, Bruce, Plastow, & Ma, 2017; and genetically modified food (Lang & Hallman, 2005). Institutional trust is often measured by asking survey respondents to evaluate food system actors (retailers, food manufacturers, farmers, government) on the basis of their competence, transparency, public interest, and honesty (as well as knowledge and credibility) with respect to a particular issue (de Jonge, van Trijp, Goddard, & Frewer, 2008).…”
Section: Trustmentioning
confidence: 99%
See 2 more Smart Citations